Evolução temporal do aleitamento materno e fórmulas infantis e da desigualdade desses indicadores em países da América Latina de 1990 a 2010 - Ferreira, Camila Silva (2020)
ABSTRACT Introduction: The prevalence of breastfeeding in Latin American countries has increased after the implementation of policies that promote, protect and support this practice. However, the market for infant formulas in these countries is expanding and studies that assess the consumption of these products are scarce, especially according to socioeconomic status. Objective: To analyze the trend of social inequality in breastfeeding practices (BF) and in the use of infant formulas (IF) in Latin America between 1990 and 2010.Methods: This is a time series study including data from the Demography and Health Survey (DHS) carried out between 1990 and 2010 in nine Latin American countries: Bolivia (1998 to 2008), Brazil (1996 to 2006), Colombia (1990 to 2010), Guatemala (1995 to 2015), Haiti (1994 to 2017), Honduras (2006 to 2012), Nicaragua (1998 to 2001), Peru (1991 to 2012) and the Dominican Republic (1996 to 2013). The indicators Exclusive Breastfeeding (EBF), BF between 6 and 12 months (BF ≥6<12), Infant formula in children under 6 months (IF <6) and between 6 and 12 months of age (IF≥6<12) were expressed as prevalence and 95% confidence interval. Inequality for BF and formulas was assessed by the angular inequality index (SII) and concentration index (CIX), with positive values representing a higher prevalence in infants with higher income and negative values in infants with lower income. The trends of BF and IF prevalences and inequality index was analyzed by linear regression models with variance-weighted least squares. Results: The prevalence of BF increased in 8 of 9 countries and infant formula in 4 of 9 countries. Brazil, Colombia and Honduras increased BF and reduced infant formula indicators. The highest annual increase for AME was in Colombia, Haiti and Nicaragua. For infant formula the largest anual increase was in Bolivia and Nicaragua, and the reduction was Brazil and Honduras. EBF was associated with the lowest income quintile, negative SII and CIX values (except Brazil and Colombia), and use of infant formula with the largest income quintile, positive SII and CIX values (except Brazil). The inequality for infant formula was reduced in 6 of the 9 countries, explained by the increase in the prevalence among infants from the lowest income quintiles, that is, infants belonging to the lowest income quintile were closer to the largest quintile in infant formula consumption. Guatemala was the only country that showed a reduction in inequality for EBF, with children belonging to the highest income quintile approaching the lowest quintile. Conclusion: The prevalence of EBF showed an increasing trend in most countries Inequality has decreased for formulas and increased for EBF in most countries. Therefore, it is essential to study health inequalities to guide public policy makers. The intensification and monitoring of actions aimed at protecting, promoting and supporting breastfeeding and reducing the consumption of breastmilk substitutes are necessary in all income groups. Keywords: Breastfeeding, Human Milk Substitutes, socioeconomic position, Demography and Health Surveys, Inequality, Latin America, International Code for Breast Milk Substitutes.